The impact of Transportation and Water Infrastructure Spending Source on Economic Growth: Evidence from U.S. State and Local and Federal Government. - Fosu, Prince; Twumasi, Martinson Ankrah (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The principal objectives of this study are to analyze the effect of state and local governments and federal government transportation and water infrastructure spending on economic growth in the United States using historic data from 1980 to 2016. The study finds that state and local governments had statistically significant impact on growth however, federal spending on transportation and water infrastructure had a strong positive and insignificant effect on economic growth. Also, shocks to infrastructure spending had a positive impact on economic growth. The study suggests raising state and local governments spending on water and transportation could have a significant impact on economic growth.